Hematological effects of feeding cassava pulp, singly and in combination with yellow corn and lime, on mature female mice (Mus musculus Linn.) - Abrenica, Sharmaine Love V. (2003)
A study was conducted to assess the toxicity of cassava pulp when fed to mature female mice using hematological parameters. Treatments used were pure yellow corn as control (To), pure dried cassava pulp (T1), pure washed cassava pulp (T2), 50% dried cassava pulp + 50% yellow corn (T3), 50% washed cassava pulp + yellow corn (T4), and dried cassava pulp with lime adjusted to pH 7.2 (T5). Thirty-six (36) mature, female mice were randomly distributed to the different treatment s using the Completely Randomized Design and were fed for a period of six weeks. Results showed significant decrease in weight of animals in treatments 1 and 2 compared to those fed with 50% mixed cassava pulp (T3 and T4) and control diets (T0). Hematological examinations revealed that cassava pulp mixed with 50% yellow corn (T3 and T4) did not have lethal effects on mice. On the other hand, animals in treatment 2 showed signs of chronic HCN poisoning like watery and bright red coloration of blood accompanied by a decrease in blood volume, longer coagulation time, presence of macrocytic cells, low lymphocyte and high neutrophil-segmented count. Abnormal physical and behavioral manifestations of poisoning were also observed before death. No hematological examinations were conducted on animals in T1 and T3 since all the mice died nine days and six days, respectively after the start of feeding. Mice in these treatments also showed abnormal manifestation pointing to chronic HCN poisoning as the cause of their death
Thesis (BS Applied Mathematics) -- University of the Philippines Mindanao, 2003